2022
DOI: 10.1177/10436596211068432
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Gerontology in Transcultural Academics: A Phenomenographic Study of Thai and Swedish Nurse Educators’ Conceptions of Gerontological Nursing

Abstract: Introduction: There is an urgent need for registered nurses with gerontological competence within long-term care (LTC) of older adults. Despite increases of life expectancy, LTC for older adults is not emphasized in nursing curricula in neither Sweden nor Thailand. Thus, the aim was to explore conceptions on gerontological nursing (GN) among Swedish and Thai nurse educators. Method: A qualitative phenomenographic method, based on open-ended interviews with five Thai and nine Swedish nurse educators was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Participants perceived that subsequent achievement of the Award strengthened their confidence to lead and advocate for gerontological nursing. This confidence may inspire the next generation of nurses to consider working with older people, which may support them to fulfil their responsibilities to direct more graduates to work in this growing field [ 6 ]. More specifically, they perceived that receiving the Award increased awareness of the importance of older adult care and education in their personal communities of practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants perceived that subsequent achievement of the Award strengthened their confidence to lead and advocate for gerontological nursing. This confidence may inspire the next generation of nurses to consider working with older people, which may support them to fulfil their responsibilities to direct more graduates to work in this growing field [ 6 ]. More specifically, they perceived that receiving the Award increased awareness of the importance of older adult care and education in their personal communities of practice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a systematic review of baccalaureate nursing students, researchers found that student preferences for working with older people decrease during training [ 5 ]. Researchers in a phenomenographic study of nurse educators in Thailand and Sweden described an ethical responsibility for nurse educators to be credible and a source of inspiration about ageing and aged care nursing in relation to global ageing [ 6 ]. Addressing nurse educators and the quality of education required to cultivate student interest in gerontology is recommended [ 5 ].…”
Section: Introductionmentioning
confidence: 99%